PERAN BALAI PEMASYARAKATAN DALAM MELAKSANAKAN BIMBINGAN TERHADAP KLIEN ANAK PEMASYARAKATAN (STUDI DI BAPAS MATARAM) - Yusri Yusri (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
Correctional Centers are institutions to carry out community guidance, in this case, it is different from Correctional Institutions where Correctional Institutions are places to carry out coaching for prisoners and correctional students. This study aims to find out how the role of guidance is carried out by the Correctional Center for clients of correctional children at the Mataram Correctional Center. This study uses a qualitative method that is descriptive. The conclusion of this study is that the Mataram Community Center in carrying out guidance has a role, namely Providing counseling and social guidance, Providing counseling and social guidance, and Conducting research on various elements of the correctional system with the aim of change.